Kegiatan Pengabdian kepada Masyarakat Pemberdayaan Komunitas Peduli Waduk Jlantah Karanganyar - Sukarno, Karmila Sari; Irawan, Andrie; Arsetyo, Yulio Iqbal Cahyo (PT. Sharia Journal and Education Center, 2026)
The Jlantah Reservoir in Karanganyar holds significant potential as a water resource and tourist attraction; however, its management requires active participation from the local community to ensure sustainability. This Community Service (PKM) activity aims to empower the Reservoir Care Community by enhancing their understanding and skills in environmental management and the utilization of creative economic potential. The methods employed include participatory socialization, environmental governance training, and mentoring in the establishment of community business units. The results of this activity indicate an increase in community awareness regarding the preservation of the reservoir's ecosystem and the formation of a collaborative framework between the community and the local government. Through this empowerment, it is expected that the Jlantah Reservoir will not only be ecologically preserved but also provide a positive economic impact on the welfare of the surrounding residents.